2014
DOI: 10.1007/s11695-014-1475-8
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic Adrenalectomy in Obese Patients: Is It Suitable?

Abstract: Dorsal retroperitoneoscopic adrenalectomy can be safely performed in morbidly obese patients, maintaining the advantages of minimally invasive surgery. Avoiding an abdominal approach is beneficial for patients. There is a more favourable postoperative course, shorter hospital stay, better cosmetic outcome and quicker recovery with dorsal retroperitoneoscopic adrenalectomy. The prolonged operative time, longer hospital stay and higher risk of postoperative complications that occurred in obese patients were acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
0
32
1
Order By: Relevance
“…The retroperitoneal approach seems to be less effective in patients with increased BMI due to the relatively thick lumbar subcutaneous layer, which leads to less effective port placement and, thus, hampered and unsafe retroperitoneal manipulation. Although Zonca et al claimed that RP is safe and effective even for patients with BMI values over 40 [22], most publications recommend TP for obese (BMI: > 30) patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal approach seems to be less effective in patients with increased BMI due to the relatively thick lumbar subcutaneous layer, which leads to less effective port placement and, thus, hampered and unsafe retroperitoneal manipulation. Although Zonca et al claimed that RP is safe and effective even for patients with BMI values over 40 [22], most publications recommend TP for obese (BMI: > 30) patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…24,26 For instance, Zon ca et al suggested that retroperitoneoscopic access can also be used safely in morbidly obese patients, and indeed might be associated with more favorable postoperative course, shorter hospital stay, better cosmetic outcome and quicker recovery. 27 In his opinion, it might also be more convenient in cases of bilateral adrenal tumors. In our center, laparoscopic transperitoneal lateral approach is the preferred access to adrenal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation affects 2–27% of the western population, but the relationship between obesity and constipation is still unclear [ 20 ]. Some authors reported no association between increasing BMI and constipation prevalence [ 21 23 ], while other authors found a higher rate of constipation in obese individuals [ 24 , 25 ]. Our study data confirmed that constipation presents a common problem in obese individuals (37.1% of patients reported symptoms of constipation and reached WCS ≥ 5 before surgery).…”
Section: Discussionmentioning
confidence: 99%